The headmistress [videorecording (DVD)] - Micklos, Christopher A.; Micklos, Christopher A.; Micklos, Christopher A.; Sapiro, Jay; Sapiro, Jay; Sapiro, Jay; Chung, Glenn; Bellantone, Katherine; Carr, Tom Dacey; Kosmatka, DeChangel; McCarthy, Tom; O'Harrow, Hunter; et al. (Indican Pictures, 2023)
"When a debt-ridden teacher inherits an abandoned lakefront inn, she and a group of potential buyers visit the property, where they discover a dark, sinister secret and a malignant supernatural presence determined to keep them there forever" -- Back of container.